2005
DOI: 10.1007/s10227-005-0145-9
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring a Remote Phototherapy Unit Via Telemedicine

Abstract: Telemedicine provided an excellent way to monitor patients receiving phototherapy in an area without a dermatologist. Overall, patient care improved: More patients were treated effectively with better outcomes and fewer side effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…VC achieves better physician and patient satisfaction and it suits best for counselling and education 12 . The dermatoses require MT for screening and triage, the purpose of diagnoses and screening a dermatoses needs SAFT, follow‐up care can be provided by SAFT or MT and counseling and education needs VC or HT 88–95 . The most common purpose of teledermatology is diagnosis.…”
Section: Design Of a Teledermatology Practicementioning
confidence: 99%
“…VC achieves better physician and patient satisfaction and it suits best for counselling and education 12 . The dermatoses require MT for screening and triage, the purpose of diagnoses and screening a dermatoses needs SAFT, follow‐up care can be provided by SAFT or MT and counseling and education needs VC or HT 88–95 . The most common purpose of teledermatology is diagnosis.…”
Section: Design Of a Teledermatology Practicementioning
confidence: 99%
“…Previous studies of individuals with psoriasis have revealed widespread dissatisfaction with treatments received, as well as frustration with current management strategies, the need for more appropriate forms of therapy, 23–25 and improved health care access and coverage 26,27 . In view of the limited Canadian data available, this survey aimed to facilitate better understanding of the severity and impact of psoriasis on Canadian patients.…”
Section: Introductionmentioning
confidence: 99%
“…Previous worldwide surveys of psoriasis affected individuals have revealed widespread dissatisfaction with available treatments, as well as frustration with current management strategies, thereby demonstrating the need for more appropriate forms of therapy (Nijsten et al, 2005, Stern et al, 2004 and the importance for an improved access for patients to health care services (Klotz et al, 2005, Simpson et al, 2006). …”
Section: Treatment Satisfaction: Results Of Worldwide Surveysmentioning
confidence: 99%